2008
DOI: 10.1029/2008gc002118
|View full text |Cite
|
Sign up to set email alerts
|

Hydroacoustic methodology for detection, localization, and quantification of gas bubbles rising from the seafloor at gas seeps from the eastern Black Sea

Abstract: [1] Detailed acoustic investigation of bubble streams rising from the seafloor were conducted during R/V Meteor cruise M72/3a at a deep submarine hydrocarbon seep environment. The area is located offshore Georgia (eastern part of the Black Sea) at a water depth between 840 m and 870 m. The sediment echosounder Parasound DS-3/P70 was used for detecting bubbles in the water column that causes strong backscatter in the echographs (''flares''). Employing the swath echsounder Kongsberg EM710 flares in the water col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 48 publications
2
96
0
1
Order By: Relevance
“…Active seepage during our recent sampling campaign was indicated by gas flares rising up to about 300 m below sea level (Nikolovska et al, 2008). The authors reported a maximum gas flux of 5.5 L min − 1 from single outlets, and Haeckel et al (2008) calculated an annual flux of dissolved methane of 2.45 ⁎ 10 6 mol for a field covering 0.31 km 2 of the Batumi seep area.…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Active seepage during our recent sampling campaign was indicated by gas flares rising up to about 300 m below sea level (Nikolovska et al, 2008). The authors reported a maximum gas flux of 5.5 L min − 1 from single outlets, and Haeckel et al (2008) calculated an annual flux of dissolved methane of 2.45 ⁎ 10 6 mol for a field covering 0.31 km 2 of the Batumi seep area.…”
Section: Geological Settingmentioning
confidence: 99%
“…7), as gas hydrates are 14 bar or almost 1.6°C, respectively, below decomposition conditions. Moreover, supply of vent gas from deep reservoirs through vertical faults (Wagner-Friedrichs, 2007) appears plausible with respect to the seepage intensity observed (Nikolovska et al, 2008). Assuming that transport of vent gas through permeable conduits proceeds with high velocity and low residence time compared to diffusive transport, LMWHC and carbon dioxide of this gas type should only be slightly affected by syn-migration alterations.…”
Section: Station Nomentioning
confidence: 99%
“…Nikolovska and Waldmann presented a study quantifying underwater gas seepage using passive acoustics (Nikolovska and Waldmann, 2006). Nikolovska and co-authors also employed a horizontally looking sonar mounted onto a ROV in order to quantify gas emission offshore Georgia at the eastern part of the Black Sea (Nikolovska et al, 2008). For gas quantification and bubble analysis, acoustic methods have the clear advantage of covering large fields of observation and not interfering hydrodynamically with the volume of observation.…”
Section: Introductionmentioning
confidence: 99%
“…The simultaneous occurrence of high amounts of gas hydrates and widespread vigorous gas ebullition observed in the area (Klaucke et al, 2006;Nikolovska et al, 2008) suggests gas transport as the major supply for methane to form gas hydrate. Our model simulations confirm this hypothesis because neither diffusion nor the low upward advection velocities constrained for the Batumi area are able to transport sufficient amounts of methane to the surface sediments to allow for considerable hydrate formation.…”
Section: Highest Ch 4 Concentrations In Shallow Anoxic Seep Sedimentsmentioning
confidence: 99%